PENATAAN KEPEGAWAIAN DI KELURAHAAN MAASING, KECAMATAN TUMINTING KOTA MANADO - GANI, NANDAR ALFIAN; RORONG, ARIE; PLANGITEN, NOVVA (JURNAL ADMINISTRASI PUBLIK, 2020)
The The purpose of this study was to determine how the staffing was arranged in the Maasing Village inManado City. The study uses a descriptive-qualitative approach. Data collection uses interview guidelines,while the analysis technique used is an interactive model analysis from Miles and Hubernann. Based onthe results of the study, conclusions (1) of the planning carried out by the Maasing Village Office wereclassified as good, seen in the arrangements of existing employees and provided them with new jobdesks;(2) the organization is quite good, carried out in accordance with the directions and instructions of theTuminitng sub-district and to carry out their duties and principals; (3) the implementation has not beensaid to be good, because in the division of tasks and the role of each employee is still very poor and doesnot understand at all the jobdesk owned by the employee. (4) the supervision carried out is quite good,seen from the decision of the lurah who makes an evaluation meeting every month and always evaluatesthe performance of his employees.Keywords: Structuring, Employee, Village.